Reconstructing rhetorical strategies from the text of Galatians - syntax-based discourse analysis as a monitoring device - G. J. Swart (Acta Theologica)
This paper focuses on areas of overlap between linguistic and rhetorical analyses of Paul’s Letter to the Galatians. The question is raised whether and to what extent conclusions drawn from a text immanent linguistic approach, on the one hand, and those drawn from rhetorical analyses, on the other, are compatible and mutually supportive. Using Galatians as sample text, the author compares three different approaches: analysis presupposing a rhetorical scheme (as proposed by Hans Dieter Betz), the reconstruction of a rhetorical strategy from the text itself (as advocated by Francois  Tolmie), and the so-called semantic (though ultimately syntactic) discourse analysis of Galatians published by a group of South African New Testament scholars. By means of this comparison, the author illustrates the value of a syntactically based method of discourse analysis for verifying conclusions regarding rhetorical strategies.